Distance Learning for Teacher Training in Brazil - Bof, Alvana Maria (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2004)
Proformação is a distance teacher certification course aimed at providing training to 27,000 uncertified teachers in 15 Brazilian states. This innovative program organizes human and technical resources for delivering distance education in a cost-effective manner. Different from other institutional systems – which typically employ their own dedicated content, design, and instructional resource personnel, and accompanied by a large pool of administrative staff – Proformação leverages pre-existing learning resources such as content experts, technology specialists, instruction, and student support systems from several institutions. Proformação goal is to create a viable teacher certification course to upgrade thousands of non-certified teachers working in the field. Proformação is coordinated by an administrative unit of the Brazilian Ministry of Education. To support the program, an information system was implemented to continuously and consistently monitor the program’s activities and results. Results of an external evaluation have been positive; Proformação is regarded by some as an innovative model for delivering decentralized training opportunities to large student numbers. Therefore, the findings in this article may prove interesting to those charged with implementing distance learning initiatives in developing countries, in that the lessons learned in Brazil may help others interested in implementing similar distance training programs.